The Effect of Modified Supplementary Feeding with Mung Bean Porridge Enriched with Ginger and Lemongrass (PMT Burjo Jase) on Weight Gain in Toddlers - Satriani, Desak; Amalia, Waifti; Rahmawati, Wenny (Media Husada Journal of Midwifery Science, 2026)
Nutrition is important for supporting the growth and development of toddlers. Providing supplementary foods made from local ingredients is one strategy for addressing nutritional problems in toddlers and preventing stunting. The purpose of this study was to determine the effect of modifying the provision of supplementary foods consisting of mung bean porridge with ginger and lemongrass on weight gain in toddlers at the Adenium RW 14 Posyandu in Sumberporong Village. The research design used a Quassy Experimental Design with a one-group pretest and posttest design. The research population consisted of 23 toddlers. Sampling was conducted using purposive sampling. The researcher required inclusion and exclusion criteria. The research was conducted over 14 days. The research instruments used were digital scales, KIA books, questionnaires, and observation sheets. The analysis used was univariate and bivariate using the Wilcoxon test. Based on the statistical test results, the significance value was 0.000, which was not greater than 0.05, meaning that there was an effect of modifying the provision of mung bean porridge with ginger and lemongrass as supplementary food on increasing the weight of toddlers at the Posyandu. The results of the study showed that the average weight gain of toddlers was 0.33 kg. It can be concluded that there is an effect of supplementary feeding on toddlers in the form of modified supplementary feeding of mung bean porridge with ginger and lemongrass. It is recommended that village midwives create various programs to improve the nutritional status of toddlers and add references to the PMT menu.